2019
DOI: 10.1002/smll.201805084
|View full text |Cite
|
Sign up to set email alerts
|

A Biodegradable and Stretchable Protein‐Based Sensor as Artificial Electronic Skin for Human Motion Detection

Abstract: such as increasing the mechanical flexibility, [3,4] sensitivity [5,6] and accuracy, [7] lowering down the operating voltage, [8,9] response speed, [1,10,11] etc. To realize the close-fitting to human bodies and the long-term monitoring, mechanical flexibility has become one of the most critical properties for wearable devices [12] and on-skin sensors. [13][14][15][16] Previously, conventional flexible devices usually applied thin polymer films as the substrates, such as poly(ethylene terephthalate), [17][18][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 42 publications
3
152
0
Order By: Relevance
“…[190,191] Films consisting of biomimetic chitin, silk, and their hybrids are also highly transparent under visible light. [110,[192][193][194] Using biomimetic chitin NFs and silk fibroin (β-sheet) with conductive AgNFs, the hybrid films show high transparency of >90% ( Figure 7c). [192] The addition of a β-sheet increases the elastic modulus up to 6.5 GPa, provided by hydrogen-bonded cross-links, while reducing the defects of the chitin NFs.…”
Section: Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…[190,191] Films consisting of biomimetic chitin, silk, and their hybrids are also highly transparent under visible light. [110,[192][193][194] Using biomimetic chitin NFs and silk fibroin (β-sheet) with conductive AgNFs, the hybrid films show high transparency of >90% ( Figure 7c). [192] The addition of a β-sheet increases the elastic modulus up to 6.5 GPa, provided by hydrogen-bonded cross-links, while reducing the defects of the chitin NFs.…”
Section: Transparencymentioning
confidence: 99%
“…[134,235,303] In addition, the wearable electronics based on skin-compatible and liquid (or water)-repellent materials should be expected to offer a long-lasting sensor capability. [110,236,239] Stauffer et al reported clinical quality of EEG recordings using soft macropillar polymer electrodes, conductive polymer with Meandering interconnection ≈800% expansion…”
Section: Electrophysiological Sensorsmentioning
confidence: 99%
“…A stretchable structure, an intrinsically stretchable conductor, and compounded conductive materials and elastomers are all widely used to implement device stretchability [52,53]. For instance, Guo and co-workers [54] developed a tactile sensor based on an electrode designed with argentum nanofibers (Ag NFs) and silk fibroin. The silk fibroin film exhibited excellent stretchability (>60%).…”
Section: Stretchabilitymentioning
confidence: 99%
“…[34] In addition to imparting flexibility to electronic devices, they also require mechanical stretchability to better interface and concurrently deform with the skin. Two strategies have been applied to achieve mechanical stretchability in soft electronics: 1) utilizing intrinsically stretchable, rubbery materials including rubbery electronic materials (semiconductors, conductors, and dielectrics) [14,15,24,[35][36][37][38][39][40][41][42][43][44][45] and liquid metals [46][47][48][49] to build the electronics; 2) employing engineered structures like wrinkles, [34,[50][51][52][53][54][55][56] serpentines, [12,17,33,44,[57][58][59][60][61] island-bridge structures, [62,63] textiles, [64] origami, [65,66] kirigami, [37,67] and microcracks [68] to accommodate the induced strain. [30,…”
Section: Strategies To Improve the Soft Electronics/skin Interfacementioning
confidence: 99%